Pengaruh Wordwall dalam Meningkatkan Minat Belajar Kosakata Bahasa Arab pada Siswa Kelas VIII di MTs Al-Muddatsiriyah Jakarta - Nurchasanah, Maryam; Fahmi, Ari Khairurrijal (UAS PRESS, 2024)
Interactive learning media will make it easier for teachers to design an effective, conducive and not monotonous learning process, so that it can also help students understand Arabic easily, one of which is the Wordwall Website media. This study aims to determine the influence of Wordwall Website media to increase interest in learning Arabic for grade VIII students Junior High School (MTs) Al Muddatsiriyah Jakarta in learning vocabulary. The study used correlational quantitative methods. Data testing uses normality test, homogeneity test and correlation test. The results of the analysis prove that the Wordwall Website media is influential in increasing the interest in learning Arabic for grade VIII students in vocabulary learning at Junior High School (MTs) Al Muddatsiriyah Jakarta. The result is obtained from the significance of 2-tailed 0.015 which value is < alpha 0.05. Then the result of testing the hypothesis is that H1 is accepted and H0 is rejected. From the results of 72 respondents of grade VIII students, it proves that the Wordwall Website media has an influence on increasing interest in learning Arabic in vocabulary learning.